Light-Field Retargeting - Birklbauer, C.; Bimber, O. (Computer graphics forum, 2012)
We present a first approach to light‐field retargeting using z‐stack seam carving, which allows light‐field compression and extension while retaining angular consistency. Our algorithm first converts an input light field into a set of perspective‐sheared focal stacks. It then applies 3D deconvolution to convert the focal stacks into z‐stacks, and seam‐carves the z‐stack of the center perspective. The computed seams of the center perspective are sheared and applied to the z‐stacks of all off‐center perspectives. Finally, the carved z‐stacks are converted back into the perspective images of the output light field. To our knowledge, this is the first approach to light‐field retargeting. Unlike existing stereo‐pair retargeting or 3D retargeting techniques, it does not require depth information.